Dimethylglycinium hydrogen maleate‒maleic acid, a new all-organic ferroelectric with an incommensurate phase - Szafrański, M.; Tylczyński, Z.; Ghazaryan, V. V.; Petrosyan, A. M. (Scientific reports, 2025)
An all-organic ferroelectric material was synthesized using maleic acid and dimethylglycine, a derivative of the simplest proteinogenic amino acid. The dimethylglycinium hydrogen maleate‒maleic acid crystal, formed of simple monocations and complex dimeric H-bonded monoanions, undergoes two phase transitions, a second-order transition at 295 K and a first-order transition at 271 K. In the high-temperature phase I of the space group Pnma , the dimethylglycinium cations are disordered; in the intermediate phase II, their site disorder transforms into incommensurate modulation; and in the low-temperature commensurately modulated phase III of the space group Pca 2 1 , the cations adopt ordered sites. The ferroelectric properties of phase III are evidenced by the polarization switching in an external electric field, as well as by the temperature and frequency dependence of the electric permittivity.